POLITIK HUKUM DALAM TRANSISI KEKUASAAN: DEMOKRATISASI PEMBANGUNAN HUKUM DARI ERA JOKOWI MENUJU PRABOWO - Haedar Ibnu Roif; Abdul Aziz Nasihuddin (Universitas Labuhanbatu, 2026)
This study examines the dynamics of legal politics in national legal development during the transition of power from the administration of President Joko Widodo to the administration of President Prabowo Subianto. The analysis focuses on the legislative process, the executive–legislative relationship in lawmaking, and the level of public participation in the formulation of legal policies. This research employs a normative legal research method using statutory, conceptual, and analytical approaches based on primary and secondary legal materials.The findings indicate that legal politics during Jokowi’s administration was characterized by accelerated legislation and regulatory simplification through the omnibus law approach, which strengthened the role of the executive in the lawmaking process but also generated debates regarding the level of public participation. Meanwhile, in the early phase of Prabowo’s administration, the direction of legal politics remains in a stage of policy consolidation influenced by the configuration of political coalitions in parliament. These conditions indicate that Indonesia’s legal politics during this transitional period reflects an ongoing balancing process between governmental effectiveness and the strengthening of the principles of the rule of law and public participation in national legal development.Keywords: Legal Politics; Power Transition; National Legal Development; Constitutional Democracy; Political Configuration